IN UNA LINGUA CHE NON SO PIU' DIRE. IL CODICE LINGUISTICO DI HORCYNUS ORCA - CARTA AMBRA (Biblioteca di via Senato Edizioni, 2019)
The article traces the genesis and the linguistic and stylistic invention of Stefano D'Arrigo's work, crossing the first production in verse with the more mature poematic construction of 1975